(untitled) (ModaPalavra e-periódico, 2018)
Color is one of the most relevant aspects of fashion products’ surfaces, which is responsible for most consumer choices. Being elaborated with 18 to 24 months in advance of the sales season, the color trends research is essential in the industrial fashion cycle, as one of the first steps in the production of a collection. This article aims to discuss how research of trends in color dialogues with sociocultural factors and with the material culture as a referential that clothes carry when inserted in a particular social context. In addition, this work brings to light the role of color trends forecasting in a fluid, ephemeral and impermanent contemporary context, regarding tastes, behaviors and styles.